Response surface methodology study on electrochemical adsorption regeneration of water-based drilling fluid waste. Issue 14 (21st September 2020) - Xie, Shuixiang; Ren, Wen; Zhang, Mingdong; Tong, Kun; Wu, Baichun; Sun, Jingwen; Liu, Xiaohui; Zhang, Zhena
ABSTRACT: This study explores an electrochemical adsorption method on the regeneration of aqueous drilling fluid waste. Response surface analysis was applied to investigating the electrochemical factors on the adsorption performance. The response surface polynomial model optimized the preferred electrochemical adsorption conditions with adsorption time of 20 min, spacing electrodes of 5 cm, adsorption concentration of 5% and NaCl concentration of 2 g/L. The model calculated electrochemical adsorption amount of drilling fluid showed only 1.3% deviation from the experimental results. Thus, the model could provide effective support for the device design and application of drilling fluid electrochemical adsorption process.